Respuesta :

Answer:

The options are not given, so I will answer in a general way:

A quadratic equation can be written, in general form, as:

y = a*x^2 + b*x + c

Then if we want this, we need to replace:

a = 1

b = -3

c = -5

Then the equation that we want is:

y = x^2 - 3*x - 5

Is likely that the options are in the factorized way to write a quadratic equation (so it is kinda harder to you)

Such that the factorized way is written as:

y = (x - k)*(x - h)

where k and h are the roots of the quadratic equation.

So you just need to expand that expression and find the one that looks like:

y = x^2 - 3*x - 5

Just to be complete, let's find the factorized form of this particular quadratic equation.

The roots are given by:

0 = x^2 - 3*x - 5

And the two solutions are given by Bhaskara's formula:

[tex]x = \frac{-(-3) \pm \sqrt{(-3)^2 - 4*1*(-5)} }{2*1} = \frac{3 \pm 5.39}{2}[/tex]

The two roots are:

h = (3 + 5.39)/2 = 4.195

k = (3 - 5.39)/2 = -1.195

Then the factorized form is:

y = (x - 4.195)*(x + 1.195)

ACCESS MORE